2020
DOI: 10.1016/j.redox.2020.101650
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide nucleotide transhydrogenase (NNT) regulates mitochondrial ROS and endothelial dysfunction in response to angiotensin II

Abstract: Endothelial dysfunction is a critical, initiating step in the development of hypertension (HTN) and mitochondrial reactive oxygen species (ROS) are important contributors to endothelial dysfunction. Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the nicotinamide nucleotide transhydrogenase ( Nnt ) gene that are associated with endothelial dysfunction and increased risk for HTN. NNT is emerging as an important enzyme that regulates mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The involvement of most of these upregulated genes in the immune response/immune modulation and the association of two (Slpi and Nnt) of these genes with AD suggests the need to investigate all of these five genes in the future as candidate genes underlying the immunomodulatory mechanism in AD [ 68 , 69 ]. Interestingly, Slpi and Nnt are known to contribute to antioxidant properties, as reported in the literature [ 70 , 71 ]. Similarly, four genes (Cd209e, D630045J12Rik, Gm10260, and Igkv8-28) were found to be downregulated in both comparative analyses.…”
Section: Discussionmentioning
confidence: 98%
“…The involvement of most of these upregulated genes in the immune response/immune modulation and the association of two (Slpi and Nnt) of these genes with AD suggests the need to investigate all of these five genes in the future as candidate genes underlying the immunomodulatory mechanism in AD [ 68 , 69 ]. Interestingly, Slpi and Nnt are known to contribute to antioxidant properties, as reported in the literature [ 70 , 71 ]. Similarly, four genes (Cd209e, D630045J12Rik, Gm10260, and Igkv8-28) were found to be downregulated in both comparative analyses.…”
Section: Discussionmentioning
confidence: 98%
“…A study using mitogen-activated protein kinase 9 (Mapk9) knockout mice demonstrated that susceptibility to acetaminophen-induced liver injury was influenced by the presence or absence of the Nnt gene defect carried by C57BL/6 mice [127]. The Nnt gene mutation in the C57BL/6J strain is a prominent phenotype-associated mutation in C57BL/6 substrains that affects protein expression in the mitochondria of many tissues and consequently many different metabolic traits [62,72,78,82,88,106,128]. The Nnt gene deletion status differs among C57BL/6J substrains, and the Nnt gene defect likely originated in C57BL/6J mice at the Jackson Laboratory after 1976 (Fig.…”
Section: Phenotypic Differences Among C57bl/6 Substrains Caused By Identified Genetic Variantsmentioning
confidence: 99%
“…Impaired mitochondrial function resulting from mitochondrial fragmentation and decreased mitochondrial autophagy can act as an upstream regulator of endothelial dysfunction [22,23]. Many physiological processes, such as endothelial cell movement, growth, proliferation, and regeneration, are highly dependent on mitochondrial function [24][25][26]. Mitochondrial damage reduces the available ATP in endothelial cells and therefore contributes to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%